Brokering justice: global indigenous rights and struggles over hydropower in Nepal. Issue 3 (3rd July 2019) - Sikor, Thomas; Satyal, Poshendra; Dhungana, Hari; Maskey, Gyanu
ABSTRACT: This article explores the dynamics of brokerage at the intersection between the justice conceptions enshrined in global norms and the notions of justice asserted in specific socio-environmental struggles. Using the case of a small hydropower project in Nepal, we trace the attempts of an indigenous activist to enrol villagers in his campaign against the background of villagers' everyday negotiations with the hydropower company. The study shows how global norms, such as indigenous peoples' rights, may fail to gain traction on the ground or even become sources of injustice in particular contexts.